Exploring Small Business Sustainability Strategies: a PRISMA-Based Systematic Review - Indra Muis (Jurnal Siber Multi Disiplin, 2025)
In the face of global environmental, economic, and social challenges, small businesses are increasingly expected to adopt sustainability-oriented strategies to ensure long-term viability. This study presents a Systematic Literature Review (SLR) guided by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) framework to explore and synthesize recent scholarly insights into sustainability strategies employed by small businesses. Using a rigorous search protocol across the Scopus database, 54 peer-reviewed articles published between 2019 and 2025 were selected and analysed. The findings reveal key thematic strategies, including eco-innovation, stakeholder engagement, circular economy practices, and the integration of digital technologies to enhance sustainable performance. The review also highlights critical internal and external drivers of strategy adoption, such as leadership orientation, regulatory pressures, and access to green finance. Despite the growing interest in sustainability, the review uncovers significant gaps in empirical studies from developing economies and in the measurement of long-term sustainability outcomes. The study contributes to the academic discourse by mapping existing knowledge, identifying future research directions, and offering practical implications for small business owners, policymakers, and sustainability practitioners.